Effects of low‐dose metformin on pre‐frailty among middle‐aged and elderly pre‐diabetic people - Chun‐Feng Huang; Ming‐Shi Shiao; Tso‐Yen Mao (Wiley, 2022)
Abstract Background Pre‐frailty has been identified as a clinically silent mechanism pre‐disposing people to frailty. The goal of this study is to investigate the impact of low‐dose metformin on pre‐diabetic pre‐frail patients (>50 years) on skeletal muscle mass, speed of gait, handgrip power, and health‐related quality of life (HR‐QoL). Methods We did a retrospective cohort study of subjects aged 50 years and older who were diagnosed with pre‐frailty (one or two criteria present based on Fried Frailty Index) and pre‐diabetes (HbA1c 5.7% to 6.4%) from May 2018 to April 2020. Subjects taking low‐dose metformin were compared with non‐metformin participants through a review of the medical records. The results were analysed at baseline and 6-12 months post‐prescription with or without metformin. All data were accompanied by a 95% confidence interval. Results One hundred and thirteen pre‐diabetic and pre‐frail subjects were recruited to metformin [the mean metformin administration was 750 (140) mg/day] (n = 58) or control group (n = 55). The average age was 66.3 (6.8) years old, with 52.2% of the population being female. The baseline demographic, nutritional, physical, and mental status data did not differ between groups. In comparison with the control group, an 8.9 (1.8) month low‐dose metformin intervention resulted in a higher skeletal muscle mass index of 1.26 (1.66) kg/m2 (P = 0.029), a faster gait speed of 0.15 (0.22) m/s (P = 0.011), and a greater handgrip strength of 2.1 (2.9) kg (P = 0.037). However, there was no difference in myostatin serum levels or HR‐QoL between groups. Conclusions Low‐dose metformin was statistically and clinically meaningful to improve the original skeletal muscle mass index, gait speed, and grip strength as part of the sarcopenia dimension, but the Euro Quality of Life‐5 Dimensions index and myostatin serum levels did not change significantly.